Apuração de responsabilidade em desfavor de contratantes e contratados da administração pública federal - práticas processuais das unidades administrativas do Ministério Público Federal - Teixeira, Rodrigo Vieira (2021)
Introduction: The public manager has the power-duty to apply administrative sanctions to contractors and contractors who commit administrative offenses, in the contracting phase or in the contractual execution phase. The administrative process to determine liability is the instrument to determine the materiality and authorship related to the practice of an administrative offense. The Federal Audit Court (TCU), as of 2011, began to recommend to managers the effective initiation of these processes. With the recommendations of the TCU, the managing administrative units (UAGs) of the Federal Public Ministry (MPF) started to institute, with greater frequency, processes to investigate possible administrative illicit practiced by companies in the contracting and contractual execution phase. The problem is that federal regulations do not establish a specific procedural rite, or rather, a sequence of procedural acts that must be followed. Thus, UAGs end up creating procedural rites in the way they believe they should be in order to respect due process of law. The main objective was to propose a procedural rite for the determination of responsibility to the detriment of contractors and contractors from the procedural practices of the MPF UAGs. In theoretical terms, the research was supported by the Bureaucratic Model. As for the methods and procedures, the applied, exploratory and qualitative approach was used, through bibliographic and documentary research. Bibliographic data collection was carried out through the internet and electronic public libraries, referring to federal and institutional regulations. The collection of documentary data was carried out in the MPF's electronic system of registration, control and management of documents, procedures and processes, covering 306 processes initiated in 2019 and with a degree of normal secrecy (nonconfidential). The observation was for the extraction of data that may evidence regulations or acts that permeate the establishment, instruction and judgment of the processes. Content analysis was carried out, with the establishment of categories created to represent the phases and procedural acts. As for the results, managers were provided with an overview of the process of determining liability to the detriment of contractors and contractors of the federal public administration, highlighting the strengths and weaknesses of the current routine of initiation, instruction and judgment of these processes within the scope of the administrative management of the 1st and 2nd instance units of the MPF. Based on the results, as a technological product, instructional material was prepared, in the form of a conclusive report, which included a procedural rite for determining liability to the detriment of contractors and contractors, with specification of phases and procedural acts, as well as standardization proposals supply in the MPF's computerized system and minimum parameters to be included in the entirety of the acts.